Grey Relational Analysis Approach In Academic Performance Comparison Of University: A Case Study Of Turkish Universities - Ertugrul, Irfan; Oztas, Tayfun; Ozcil, Abdullah; Oztas, Gulin Zeynep (European Scientific Journal, ESJ, 2016)
Universities, serve humanity with either the people that educate or their scientific activities. Therefore, students for a quality education and better career and scientists for the advancement of humanity by contributing to the science world need to prestigious universities. To be considered as a reputable university it must be one of the best performing universities in the area. Each year, the data about the ranking of universities are published and shared by various organizations, as worldwide or regional. Grey System theory, has been used successfully in cases where uncertainty or partial information exists. Grey Relational Analysis (GRA) is a part of Grey System theory. In this method, the correlation between reference sequence and comparability sequences is obtained and then ranking is made according to this correlation. In the study 10 Turkish University were analyzed with Grey Relational Analysis and the results of this method were interpreted.